Re-discussion on the rationality of high income of monopoly industries: Evidence from the employer-employee matched data - Haifeng Nie; Ximing Yue (China Finance and Economic Review, 2017)
Background: Industrial income differential is the most important cause of the public dissatisfaction with the income inequality in China. The high income of monopoly industries is now the typical one of the massive income inequity phenomena. But objectively speaking, not all high income of monopoly industries is unreasonable. The income differential caused by employees' education level is reasonable in a certain range. Measuring and analyzing the high income of monopoly industries should be based on taking various elements such as employees' education level and working age into account. Methods: Using the employer-employee matched data, we overcome the problem of missing variables and make the estimates of unreasonable parts of the high income of monopoly industries more reliable. By the decomposition method, the wage gaps between monopoly and competitive industries are decomposed into the reasonable part and the unreasonable part. Results: On the average level, nearly half of the average wage difference between monopoly and competition industry is unreasonable, which is caused by monopolization. From the view of income levels, the income gaps between monopoly industry and competitive industry get widened as the income quantile increases. Specifically, at the quantile points of 10, 50, and 90%, the income gaps are 9.4, 52, and 60.6% respectively and the proportions of the unreasonable part are 26, 71, and 72% respectively. Conclusions: The gap between the monopoly industries and competition industries is robust facts. The different decomposition method gives a consistent picture that the monopoly is the important source of the income gap. The most import source of income difference comes from the structural difference of return between the monopoly industries and competition industries.
Keywords: 330; Salary differential; Oxaca-Blinder decomposition; Decomposition of quantile distribution